2010
DOI: 10.1002/ar.21265
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of the Lumbar Transversospinal Muscles Examined in a Mouse Bearing a Muscle Fiber‐Specific Nuclear Marker

Abstract: Although the morphology of human lumbar transversospinal (TSP) muscles has been studied, little is known about the structure of these muscles in the mouse (Mus musculus). Such information is relevant given mice are often used as a ''normal'' phenotype for studies modeling human development. This study describes the gross morphology, muscle fiber arrangement, and innervation pattern of the mouse lumbar TSP muscles. A unique feature of the study is the use of a transgenic mouse line bearing a muscle-specific nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
2
2
0
Order By: Relevance
“…The present S100 immunohistochemistry demonstrated a band‐like arrangement of motor endplates similar to that in the mouse lumbar transversospinalis muscle shown by Cornwall et al. (2010).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The present S100 immunohistochemistry demonstrated a band‐like arrangement of motor endplates similar to that in the mouse lumbar transversospinalis muscle shown by Cornwall et al. (2010).…”
Section: Discussionsupporting
confidence: 76%
“…The present S100 immunohistochemistry demonstrated a band-like arrangement of motor endplates similar to that in the mouse lumbar transversospinalis muscle shown by Cornwall et al (2010). S100-positive intramuscular nerve twigs exhibited downward courses, not only in the semispinalis muscle but also (because they are independent of nerve twigs to the semispinalis) through the multifidus and rotatores muscles.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…Indeed, the structure of the MF+ Scer may be affected by spinal cord compression and specific nerve root, 27 which could be a plausible explanation for the observed increase in fatty infiltration and atrophy of the paraspinal muscles at the level of spinal cord compression. Cornwall et al 28 reported that muscular bundles of paraspinal muscle extending across 2 or 3 segments do not have consecutive/in-series architecture, and that multisegmental nerves are unlikely to supply a single muscle bundle of the paraspinal muscle. Polysegmental innervation for lumbar MF muscle has been argued in several studies, however there is no such evidence of cervical MF muscle innervation.…”
Section: Discussionmentioning
confidence: 99%